Thematic harmony of words which are similar in wording according to the Quranic order (The prostrate before Adam in particular) - Mahmood, Khawla Mohammed Raja; Al-Daqour, Suleiman Muhammad (Journal of Islamic Sciences, 2022)
This study aimed at highlighting the thematic harmony between Quranic verses that have similar wordings related to the story of prostration to Adam, may peace be upon him, by tracing and tracking the verses of prostration according to the holy Quran order, and showing the relation and link between the verses despite their remote distance and their order in the chapters of the holy Quran and the revelation of these chapters in order to show the compatibility in the Quranic meaning. This study is organized into an introduction, discussion, and conclusion. The researcher uses the inductive approach to collect verses using similar words related to the prostration of angels to Prophet Adam according to the holy Quran order. The analytic approach is used to show the significance of prostration. The critical approach is also used to present, discuss, and criticize the viewpoints of some scholars regarding prostration in order to attain new meanings that this research study will reveal. This study concludes positive results represented by addressing, in order, the similar verses which are consistent with the content of the topic which gave different connotations from the revelation order, the objective order, or the contextual significance which pushes the holy Quran against the suspicions of doubts over repetition, synonyms or antonyms between similar verses. It is rather an overview and detailed explanation, generalization and particularization, clarification and supplementation, and order in events and scenes.